MCMC approach to modelling queuing systems - Landauskas, Mantas; Valakevičius, Eimutis (Lietuvos matematikos rinkinys, 2010)
The paper presents some numerical results on modelling a M/G/1/∞ queuing system using Markov chain Monte Carlo (MCMC). This particular technique was chosen in order to draw samples from the service time distribution from which it is assumed complicated to sample random numbers. The software for experiments was created using C++ Builder development environment.
Keywords: Queuing system; Markov chain Monte Carlo